Physical exercise modifies the functional capacity of elderly patients on hemodialysis - Moane Marchesan; Rodrigo de Rosso Krug; José Raphael Leandro da Costa e Silva; Aline Rodrigues Barbosa; Airton José Rombaldi
Abstract Introduction Patients on hemodialysis (HD) improve functional capacity after physical training. However, little is discussed about these effects in elderly patients, since these are usually excluded of studies, due to their physical disabilities and other deficits. Objective To analyze the effects of aerobic and resistance training in the functional capacity of elderly patients submitted to HD. Methods Studied participants were 15 patients, of both genders, and aged over 60 years. Aerobic and resistance training was carried out during the hemodialysis session, three times per week, during four months. Patients were distributed into control (CG) and experimental (EG) groups. Functional capacity was assessed by six-minute walk (6MW), sit-to-stand (STS) and respiratory muscle strength tests. Results After the physical training, EG presented a significant increase in the distance covered in 6MW (Z = 2.521, p < .012), respiratory muscle strength (inspiratory pressure: Z = 2.533, p < .011; expiratory pressure: Z = 2.536, p < .011); and in number of STS repetitions (2.54; p <.001). Conclusion The training modified the functional capacity of the HD patients, contributing to their rehabilitation.